ADDRESSING HYPERTENSION IS CRUCIAL TO MITIGATING COGNITIVE DECLINE AND IMPROVING PATIENTS' QUALITY OF LIFE - Pangestuti, Dewi; Lubis, Adhayani; Lubis, Adi Raja Brando; Mukminin, Amirul; Dania, Ira Aini; Saputra, Donalry Agus; Sajow, Stenly Hely (LPPM Universitas Jambi, 2025)
Hypertension, a condition characterized by persistent elevated blood pressure, often places individuals at risk of developing complications that can adversely impact their quality of life. One notable complication associated with hypertension is cognitive dysfunction. A study published in the Journal of Alzheimer's Disease (2020) demonstrated that individuals with long-standing hypertension exhibited an elevated risk of developing cognitive impairment and Alzheimer's disease. Preliminary research suggests that approximately 12.5 percent of hypertensive deaths may be attributable to underlying factors. Aims: This study aims to examine the cognitive deficits in patients with hypertension and summarise research on the relationship between hypertension and cognitive impairment. This analytical research study with a cross-sectional design, total sample of 84 individuals who suffer from hypertension, the ages of 60 and 79 years old. The sample selected using purposive sampling, instruments used in this study were medical record and Mini Mental State Examination (MMSE) questionnaire. The data was analyzed univariate and bivariate with the Chi Square statistical test. The MMSE cognitive function test revealed that out of 84 individuals with hypertension, 67.85% had normal cognitive function, while 32.14%) moderate cognitive impairment. The sample for the research consisted of 40 male individuals (47.61%) and 44 female individuals (52.38%). Hypertension can affect a person's cognitive function which has an impact on quality of life.